2023
DOI: 10.4162/nrp.2023.17.4.789
|View full text |Cite
|
Sign up to set email alerts
|

Association of coffee consumption with type 2 diabetes and glycemic traits: a Mendelian randomization study

Abstract: BACKGROUND/OBJECTIVES Habitual coffee consumption was inversely associated with type 2 diabetes (T2D) and hyperglycemia in observational studies, but the causality of the association remains uncertain. This study tested a causal association of genetically predicted coffee consumption with T2D using the Mendelian randomization (MR) method. SUBJECTS/METHODS We used five single-nucleotide polymorphisms (SNPs) as instrumental variables (IVs) associated with habitual coffee … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 60 publications
(85 reference statements)
1
2
0
Order By: Relevance
“…The digestive enzyme binding with GCBE is inactivated, reducing blood sugar levels. Therefore, the present results indicate that GCBE is a potential compound to act against hyperglycemia, consistent with results reported in previous studies in vitro, in vivo, and in clinical trials [13,35,37] Macrophages are usually used as a model to study the anti-inflammatory effect of drugs or plant extract because they are the principal immune cells responsible for inflammation of various organs. Macrophages produce cytokines and reactive oxygen species (ROS), producing oxidative stress and increased activation of the inflammation pathway [38].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The digestive enzyme binding with GCBE is inactivated, reducing blood sugar levels. Therefore, the present results indicate that GCBE is a potential compound to act against hyperglycemia, consistent with results reported in previous studies in vitro, in vivo, and in clinical trials [13,35,37] Macrophages are usually used as a model to study the anti-inflammatory effect of drugs or plant extract because they are the principal immune cells responsible for inflammation of various organs. Macrophages produce cytokines and reactive oxygen species (ROS), producing oxidative stress and increased activation of the inflammation pathway [38].…”
Section: Discussionsupporting
confidence: 93%
“…Across the world, coffee is a popular beverage for adults, with many beneficial effects on health, including reduced incidence of diabetes, metabolic syndrome, and cancer [11,12]. Prior studies [13][14][15][16][17] have reported that coffee consumption is related to a lower risk of T2D, as observed by blood glucose levels or biomarkers in patients and animal models. Some studies indicate the ability of coffee extract, coffee components (chlorogenic acid, CGA; caffeine, CE; and caffeic acid, CA) [18][19][20][21], and green coffee bean extract (GCBE) to improve glucose and lipid metabolism [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the execution of randomized controlled trials (RCTs) encounters an array of practical limitations that render their implementation within clinical environments a formidable undertaking (23). Mendelian randomization (MR) emerges as an analytical methodology aimed at examining potential causal links between exposures and outcomes, utilizing data derived from genome-wide association studies (GWAS) (23)(24)(25)(26)(27)(28). MR uses exposure-related genetic variations as instrumental variables (IVs) and follows the Mendelian gamete random allocation principle as well as the principle of free combination.…”
Section: Introductionmentioning
confidence: 99%